Equality and Devolution in the United Kingdom: A Story in Three Acts and a Sequel. Issue 4 (8th October 2022) - Devine, Paula; Kelly, Grace; McAuley, Martina
Abstract : Within the United Kingdom (UK), many of the arguments driving devolution and Brexit focused on equality. This article assesses how notions of equality have been shaped over the past two decades. Using a chronology of theoretical, political and public interpretations of equality between 1998 and 2018, the article highlights the shifting positions of Northern Ireland (NI) and the rest of the UK. NI once led the way in relation to equality legislation, and equality was the cornerstone of the Good Friday/Belfast peace agreement. However, the Equality Act 2010 in Great Britain meant that NI was left behind. The nature of future UK/EU relationships and how these might influence the direction and extent of the equality debate in the UK is unclear. While this article focuses on the UK, the questions that it raises have global application, due to the international influences on equality discourse and legislation.